2014
DOI: 10.1007/978-94-017-9245-5_14
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Ligand-Protein Networks in Traditional Chinese Medicine: Current Databases, Methods and Applications

Abstract: The traditional Chinese medicine (TCM), which has thousands of years of clinical application among China and other Asian countries, is the pioneer of the "multicomponent-multitarget" and network pharmacology. Although there is no doubt of the efficacy, it is difficult to elucidate convincing underlying mechanism of TCM due to its complex composition and unclear pharmacology. The use of ligand-protein networks has been gaining significant value in the history of drug discovery while its application in TCM is st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 130 publications
(52 reference statements)
0
6
0
Order By: Relevance
“…Studies indicated that the extracts and compounds from Traditional Chinese medicines suppressed the EMT ( Zhao and Wei, 2015 ), proliferation and migration of different cancer cells by inhibiting CFL1 signaling pathway in different cancer cells ( Wang et al, 2017 ; Liu et al, 2018 ). The Garcinia species from Guttiferae family have been studied for nearly 80 years ( Lu et al, 2020 ; Wu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies indicated that the extracts and compounds from Traditional Chinese medicines suppressed the EMT ( Zhao and Wei, 2015 ), proliferation and migration of different cancer cells by inhibiting CFL1 signaling pathway in different cancer cells ( Wang et al, 2017 ; Liu et al, 2018 ). The Garcinia species from Guttiferae family have been studied for nearly 80 years ( Lu et al, 2020 ; Wu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…With the advent of the era of big data, now there are large amounts of data about known and predicted protein interactions 12 . Once we use network pharmacology to predict potential targets of active components in Traditional Chinese Medicine (TCM) formula 13 , a component-target protein-related protein-metabolite network can be constructed with the combination of network pharmacology and metabolomics. As a combination of approaches is most likely to bear fruit, the combination of network pharmacology and metabolomics called network analysis could increase the degree of accuracy of target identification of network pharmacology.…”
mentioning
confidence: 99%
“…The death of dopaminergic neurons involves complex pathogenic factors and pathological mechanisms, suggesting that it is di cult for drugs with a single target to achieve a satisfactory therapeutic effect in the treatment of PD. Traditional TCM has a long application history in China and other Asian countries, besides, TCM is considered the pioneer of "multicomponent and multi-target pharmacology" [53]. Based on the theory of TCM, PD belongs to the category of tremble syndrome which considers de ciency of body caused by old age, liver and kidney de ciency, and wind evil stirring internally caused by tendons dystrophy as its etiology.…”
Section: Discussionmentioning
confidence: 99%